Digital Education Instruments for University Level Within Environmental Economics Under COVID-19 Pandemic - Igor A. SIKAREV; Valery M. ABRAMOV; Mikhail B. SHILIN; Oleg I. SHEVCHUK; Alexander S. AVERKIEV; Sergey V. LUKYANOV; Vladimir A. BOLSHAKOV; Oksana PETRIEVA; Yuri Yu. SMIRNOV; Olga N. MANDRYKA (Communications of International Proceedings, 2021)
Presented development results of digital education instruments for university level within environmental economics during Industry 4.0 period under conditions of climate change and COVID-19 pandemic. The research fundament are web technologies and building database methods. As research result, it is recommended the using of remote sensing and modelling data in university practical learning to increase the efficiency and reliability of university education within environmental economics. As digital education instruments, it is proposed the using of aggregate modular expert systems with geoinformation digital online platforms, as modules, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks. As study results, some usage examples of developed digital education instruments are demonstrated. The presented in article research results have significant scientific novelty and can be useful for different stakeholders in educational area. In research for preliminary discussion and data exchange, platform https://www.researchgate.net/profile/Valery_Abramov2/ was used.
Keywords: education instruments; university level; environmental economics; COVID-19